Bioactive cassane diterpenoids from the seeds of Caesalpinia sappan. (December 2017) - Zhu, Nai-Liang; Xu, Xu-Dong; Hu, Mei-Geng; Sun, Zhong-Hao; Wu, Tong-Yu; Yuan, Jing-Quan; Wu, Hai-Feng; Tian, Yu; Li, Peng-Fei; Yang, Jun-Shan; Ma, Guo-Xu
Graphical abstract: Highlights: Three new cassane-type diterpenoids were obtained from the seeds of Caesalpinia sappan . Their structures were characterized by extensive 2D-NMR studies. All of the isolated compounds were tested for their antimalarial and anti-inflammatory activities. Abstract: Three new cassane-type diterpenoids named caesalppans G-I(1–3) together with three known ones (4 –6 ), were isolated from the methanol extract of Caesalpinia sappan seeds. Their structures were determined based on spectroscopic data. Among the isolated compounds, compound2 displayed a moderate antimalarial activity with an IC50 value of 2.4 μM, and compound4 showed mild anti-inflammatory activity with an IC50 value of 28.65 μM.